The City and Region Against the Backdrop of Totalitarianism : Images from the Life in the Slovak Republic (1939–1945), Illustrated by the City of Nitra and Its Surroundings - Palárik, Miroslav (Studies in politics, security and society, 2018)
"The book draws attention to the manifestation of the totalitarian regime in Slovakia during World War II on the lower level of state administration. It shows how the decisions of the central government influenced the lives of ordinary citizens in their political, economic, social, and cultural life as well as in their leisure time possibilities"--